Pyriproxyfen Exposure Impairs Cognitive Parameters and Alters Cortisol Levels in Zebrafish - Gusso, Darlan; Reolon, Gustavo Kellermann; Gonzalez, Jonas Brum; Altenhofen, Stefani; Kist, Luiza Wilges; Bogo, Mauricio Reis; Bonan, Carla Denise (Frontiers in Behavioral Neuroscience, 2020)
Pyriproxyfen is one of the most used larvicides and insecticides; it acts as an analog of juvenile insect hormone (a growth regulator). It is highly toxic during all stages of mosquito development, suppresses metamorphosis, and interferes in insect reproduction and proliferation. Pyriproxyfen and its main metabolite have been shown to affect brain development in rodents. This compound is employed mainly to eliminate outbreaks of the genus Aedes, even in potable water. Despite the increasing number of toxicological studies about larvicides and insecticides—with an indication of continuous use—there have been few studies about the effects of pyriproxyfen in non-target species such as fish. This study evaluated the effects of pyriproxyfen on behavioral, cognitive, and endocrine parameters in zebrafish. We exposed adult zebrafish to different pyriproxyfen (Pestanal®) concentrations (0.125, 0.675, and 1.75 mg/L) for 96 h. We analyzed behavioral parameters, memory, cortisol levels, and gene expression of gr (glucocorticoid receptor) and crf (corticotrophin-releasing factor) after pyriproxyfen exposure. This exposure did not alter locomotion (distance or mean speed), anxiety-like behavior (latency to enter to the top zone of the tank or time in the top zone of the tank), and social or aggressive behavior. However, there was impaired inhibitory avoidance memory at all tested pyriproxyfen concentrations. Cortisol levels were reduced in exposed groups when compared to control or vehicle. However, gr and crf gene expression in pyriproxyfen-treated animals were unaltered when compared to control or vehicle groups. Taken together, these findings indicate that pyriproxyfen may induce cognitive impairment and altered cortisol levels in zebrafish, a non-target species.